NOD2 agonist murabutide alleviates radiation‐induced injury through DNA damage response pathway mediated by ATR. Issue 11 (3rd May 2019) - Liu, Lei; Qu, Hongjin; Qin, Hongran; Yang, Yanyong; Liao, Zebin; Cui, Jianguo; Gao, Fu; Cai, Jianming
Abstract: Injury‐induced by ionizing radiation (IR) severely reduces the quality of life of victims. The development of radiation protectors is regarded as one of the most resultful strategies to alleviate damages caused by IR exposure. In the present study, we investigated the radioprotective effects of the agonist of nucleotide‐binding‐oligomerization‐domain‐containing proteins 2 called murabutide (MBD) and clarified the potential mechanisms. Our results showed that the pretreatment with MBD effectively protected cultured cells and mice against IR‐induced toxicity and the pretreatment with MBD in vitro and in vitro also inhibited apoptosis caused by IR exposure. The downregulation of γ‐H2AX and the upregulation of ATR signaling pathways by MBD treatment indicated that the radioprotective effects of MBD were due to the stimulation of DNA damage response (DDR) pathway to repair DNA double‐strand breaks caused by IR exposure. As the radioprotective effects of MBD were diminished by the ATR selective inhibitor rather than the ATM inhibitor, ATR pathway was confirmed to be a more crucial checkpoint pathway in mediating the stimulation of DDR pathway by MBD. Taken together, our data provide a novel and effective protector to relieve the injury induced by IR exposure. Abstract : The stimulation of nucleotide‐binding‐oligomerization‐domain‐containing proteins 2 by murabutide (MBD) facilitates the DNA damage repair pathway upon ionizing radiation exposure, and the ATR signal is a crucial checkpoint pathway for DNA damage response induced by MBD.